Acute Aortic Thrombosis and Antithrombin III Deficiency in the Nephrotic Syndrome: A Case Report - Murphy, J. Peter (1985)
A 25-year-old Oriental woman with nephrotic syndrome was admitted to the United States Naval Hospital in Okinawa. She had acute aortic thrombosis, which was managed initially with bilateral femoral thrombectomy and calf fasciotomies. In the early postoperative period, increasing doses of heparin were required to maintain adequate anticoagulation. Hematologic evaluation revealed a deficiency of antithrombin III (AT-III). Such a deficiency has been recognized as occurring in nephrotic syndrome, most probably due to urinary loss of this serum protein. Five prior cases of acute aortic thrombosis have been described in the nephrotic syndrome, but only three reports of acute aortic thrombosis have been attributed to documented AT-III deficiency. Acute thrombosis due to AT-III deficiency may be confirmed by measuring decreased serum levels of this protein. Treatment is initiated with fresh frozen plasma and heparin, with subsequent utilization of oral warfarin.